2016
DOI: 10.1002/app.44469
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically controlled fibrillation under combination of ionic liquid with mechanical grinding

Abstract: Combination of mortar grinder mill (MG) and ionic liquid (IL) treatment was employed in order to fibrillate fibers from oil palm mesocarp fiber (OPMF) in one-step. The structural changes of OPMF before and after the treatment were examined by Thermogravimetric analysis (TGA), Fourier transformed infrared (FT-IR) spectra, Wide-angle X-ray diffraction (WAXD), Dynamic light scattering (DLS) and Scanning electron microscopy (SEM). Compared with the only use of 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM[BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In our previous study, we reported that the combination treatment (M-IL) on OPMF also alters the fiber diameter (127 nm), and when ionic liquid dissolves some components of OPMF, the magnetic grinder pulverizes the fiber at the same time. 19 Here, in the case of treatment of [OPMF-VASP], it was reported that the same pulverization effect of the magnetic grinder on the grafted OPMF fibers also provided fibrillation (105 nm). It was expected that the agglomeration of the product particles was inhibited during the wet mortar grinding in the presence of ionic liquid when compared to dry mortar grinding, 20 since the ionic liquid, 1-butyl-3-methylimidazolium fluoroborate ([BMIM][BF4]), facilitates to break down the possible hydrogen bonding among the grafted lignocellulosic components through its poorly coordinated ions.…”
Section: Resultsmentioning
confidence: 96%
“…In our previous study, we reported that the combination treatment (M-IL) on OPMF also alters the fiber diameter (127 nm), and when ionic liquid dissolves some components of OPMF, the magnetic grinder pulverizes the fiber at the same time. 19 Here, in the case of treatment of [OPMF-VASP], it was reported that the same pulverization effect of the magnetic grinder on the grafted OPMF fibers also provided fibrillation (105 nm). It was expected that the agglomeration of the product particles was inhibited during the wet mortar grinding in the presence of ionic liquid when compared to dry mortar grinding, 20 since the ionic liquid, 1-butyl-3-methylimidazolium fluoroborate ([BMIM][BF4]), facilitates to break down the possible hydrogen bonding among the grafted lignocellulosic components through its poorly coordinated ions.…”
Section: Resultsmentioning
confidence: 96%
“…Tensile and flexural tests of the nanocomposite specimens were conducted using a compact tensile and compression tester IMC-18E0 (Imoto Machinery Co., Ltd., Kyoto, Japan). The tensile properties consisted of tensile strength, Young's modulus, toughness and elongation at break were evaluated from stress-strain curves measured at a crosshead speed of 5 mm/min [24]. The flexural test was performed according to ASTM D790 on rectangular standard samples with dimension size of 120 mm × 12.7 mm and 3 mm thickness.…”
Section: Mechanical Analysismentioning
confidence: 99%
“…However, these polymers have limited thermal stability, mechanical strength, and low degradation rate [10][11][12]. In addition to biodegradable polymers, polymer materials filled with lignocellulosic materials as renewable reinforcements have also been studied extensively [13][14][15][16][17]. Despite the significant advantages of lignocellulosic materials as filler, these polymer composites cannot still be considered sustainable materials.…”
Section: Introductionmentioning
confidence: 99%